Komparasi Hasil Uji Komprehensif antara Mahasiswa Santri dan Non Santri di Universitas Islam Zainul Hasan Genggong - Abdus Sakur Fanani; Endah Tri Wisudaningsih; Nur Fatimah (ISLAMIKA, 2023)
In this study, the researcher aimed to find out whether there were differences in comprehensive test results between “santri” and “non-santri” in Zainul Hasan Genggong.Islamic University. Researcher use a quantitative approach with a comparative type of research. The population in this study was all students of Zainul Hasan Genggong Islamic University `at 7th grade of 2019. Sampling using Simple Random Sampling technique. The sample taken was a student Study Program Islamic Education with a total of 112 students. The data obtained are the results of the comprehensive test value. After that, the data obtained is analyzed using the SPSS application, (Statistical Program For Cocial Science) 16.0 for windows. The results of the study can be concluded that the average score obtained by “santri” is 87.83. While the average score of “non-santri” is 84.83. The results of the hypothesis test using the Independent Sample T Test obtained values of 0.248 > 0.05. Than, it can be concluded that there is no difference in comprehensive test results between between “santri” and “non-santri” in Zainul Hasan Genggong Islamic University.